Nicotinamide adenine dinucleotide phosphate (reduced) oxidase 2 modulates inflammatory vigor during nonalcoholic fatty liver disease progression in mice. Issue 5 (24th March 2018) - Mukherjee, Rajib; Moreno‐Fernandez, Maria E.; Giles, Daniel A.; Cappelletti, Monica; Stankiewicz, Traci E.; Chan, Calvin C.; Divanovic, Senad
Abstract : Elevated levels of reactive oxygen species (ROS) and exacerbated inflammatory responses are both implicated in NAFLD progression and subsequent hepatocellular damage. However, the role of NOX2‐dependent ROS in regulation of immune cell function and inflammatory vigor in NAFLD remains underdefined. Here we demonstrate that NOX2 expression was sufficient to impact ROS production by immune cells and to uncouple obesity from obesity‐associated glucose dysmetabolism and NAFLD. Abstract : Nonalcoholic fatty liver disease (NAFLD) represents a disease spectrum ranging from benign steatosis to life‐threatening cirrhosis and hepatocellular carcinoma. Elevated levels of reactive oxygen species (ROS) and exacerbated inflammatory responses have been implicated in NAFLD progression. Nicotinamide adenine dinucleotide phosphate (reduced) oxidase 2 (NOX2; also known as gp91 Phox ), the main catalytic subunit of the nicotinamide adenine dinucleotide phosphate (reduced) oxidase complex, modulates ROS production, immune responsiveness, and pathogenesis of obesity‐associated metabolic derangements. However, the role of NOX2 in the regulation of immune cell function and inflammatory vigor in NAFLD remains underdefined. Here, we demonstrate that obesogenic diet feeding promoted ROS production by bone marrow, white adipose tissue, and liver immune cells. Genetic ablation of NOX2 impeded immune cell ROS synthesis and was sufficient to uncouple obesity from glucose dysmetabolism and NAFLD pathogenesis. Protection from hepatocellular damage in NOX2‐deficient mice correlated with reduced hepatic neutrophil, macrophage, and T‐cell infiltration, diminished production of key NAFLD‐driving proinflammatory cytokines, and an inherent reduction in T‐cell polarization toward Th17 phenotype. Conclusion : Current findings demonstrate a crucial role of the NOX2–ROS axis in immune cell effector function and polarization and consequent NAFLD progression in obesity. Pharmacologic targeting of NOX2 function in immune cells may represent a viable approach for reducing morbidity of obesity‐associated NAFLD pathogenesis. ( Hepatology Communications 2018;2:546‐560)